Veterinary teaching in COVID-19 times: perspectives of university teaching staff - Kanwischer, Miriam; Tipold, Andrea; Schaper, Elisabeth (Frontiers in Veterinary Science, 2024)
The digitalization of university teaching has been taking place for many years and, in addition to traditional teaching formats such as practicals and face-to-face lectures, more and more e-learning courses have been used in veterinary education for several years. In the context of the COVID-19 pandemic, universities across Germany had to switch to an ad-hoc, purely digital summer semester. This study evaluated the experiences and implementation of the digital summer semester 2020 at the University of Veterinary Medicine Hannover (TiHo) Foundation from the perspective of the teaching staff. In addition to the technical equipment used by lecturers, this survey also focused on the effects of the digital semester on teaching and the future practicality of digital teaching formats and strategies in veterinary education. Therefore, a questionnaire was designed and distributed among lecturers involved in the digital summer semester 2020. One hundred and three completed questionnaires were evaluated.The results of the evaluation show that teachers see huge potential in blended learning as a teaching method in veterinary education. In addition, teachers were able to digitize teaching well with the available hardware and software. The teaching staff saw difficulties above all in the loss of practical training and in the digitalization of practical exercises. Teachers also needed significantly more time to plan and implement digital teaching compared to pure face-to-face teaching.In summary blended learning offers many advantages, such as increased flexibility for students and teaching staff. In order to be able to use digital teaching methods and strategies profitably in veterinary education in the future, well thought-out didactic concepts and further technical expansion of the universities are required. In addition, the digital skills of teaching staff should be further trained and promoted.